2012
DOI: 10.1007/s13760-012-0166-2
|View full text |Cite
|
Sign up to set email alerts
|

Preventive effect of vitamin D3 supplementation on conversion of optic neuritis to clinically definite multiple sclerosis: a double blind, randomized, placebo-controlled pilot clinical trial

Abstract: Multiple sclerosis (MS) presents with optic neuritis (ON) in 20 % of cases and 50 % of ON patients develop MS within 15 years. In this study, we evaluated the preventive effects of vitamin D3 administration on the conversion of ON to MS (primary outcome) and on the MRI lesions (secondary outcome) of ON patients with low serum 25 (OH) D levels. Thirty ON patients (15 in each of 2 groups, aged 20-40 years) with serum 25 (OH) D levels of less than 30 ng/ml were enrolled in a double blind, randomized, parallel-gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 17 publications
2
34
0
1
Order By: Relevance
“…On the other hand, two other trials reported no difference in any of these parameters (50, 52). Vitamin D supplementation might also be important in the pre-MS stage, since cholecalciferol supplementation decreased the conversion rate of optic neuritis to chronic MS (53). …”
Section: Vitamin D As a Therapeutic Agent In Human Autoimmune Diseasesmentioning
confidence: 99%
“…On the other hand, two other trials reported no difference in any of these parameters (50, 52). Vitamin D supplementation might also be important in the pre-MS stage, since cholecalciferol supplementation decreased the conversion rate of optic neuritis to chronic MS (53). …”
Section: Vitamin D As a Therapeutic Agent In Human Autoimmune Diseasesmentioning
confidence: 99%
“…With respect to prevention of MS, there have been two previous studies. The first was a randomized controlled trial in Iran of 30 optic neuritis patients given 50,000 IU vitamin D 3 per week for 12 months (24). There were significantly fewer cases of a second demyelinating attack measured on MRI in the treated group.…”
Section: Why Establish Phocis While a Trial Of Oral Vitamin D Supplemmentioning
confidence: 99%
“…The authors evaluated the clinical effectiveness of vitamin D supplementation in four systematic reviews (2730), eight randomized controlled trials (24, 3137), and three non-randomized studies (25, 38, 39). The authors of the CADTH Rapid Report concluded that “the outcomes of vitamin D supplementation for MS were heterogeneous, conflicting and inconsistent, with no effect on disability scores and relapse rates.…”
Section: Why Establish Phocis While a Trial Of Oral Vitamin D Supplemmentioning
confidence: 99%
“…A recent systematic review and meta‐analysis included the following eligible placebo‐controlled randomized clinical trials of patients with CIS: the Early Treatment of Multiple Sclerosis study (ETOMS), the Early Glatiramer Acetate Treatment in Delaying Conversion to Clinically Definite Multiple Sclerosis in Subjects Presenting with a Clinically Isolated Syndrome study (PreCISe) and the Oral Teriflunomide for Patients with a First Clinical Episode Suggestive of Multiple Sclerosis study (TOPIC); the results of this meta‐analysis showed that DMD including interferon β‐1a SC, glatiramer acetate and teriflunomide appear to attenuate brain atrophy over time when compared with placebo in patients with CIS . As discussed earlier, low vitamin D levels could be a risk factor for the conversion from CIS to clinically definite MS, and a small randomized control trial has suggested that vitamin D supplementation might reduce the risk of developing MS after CIS …”
Section: Clinically Isolated Syndromementioning
confidence: 99%
“…42 As discussed earlier, low vitamin D levels could be a risk factor for the conversion from CIS to clinically definite MS, and a small randomized control trial has suggested that vitamin D supplementation might reduce the risk of developing MS after CIS. 48 As with RIS earlier, there is a question about whether treatments with DMD for patients with CIS should be initiated as early as possible. Randomized, placebo-controlled trials were carried out to evaluate the use of interferon b, [49][50][51][52] glatiramer acetate, 53 teriflunomide 47 and cladribine 54 for patients with CIS at high risk of developing clinically definite MS as defined by MRI criteria (Table 4).…”
Section: And the Oral Teriflunomide For Patients With A First Clinicamentioning
confidence: 99%